2018
DOI: 10.3390/molecules23051148
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene and 4′-Methoxyresveratrol Inhibited Lipopolysaccharide-Induced Inflammatory Response in RAW264.7 Macrophages

Abstract: Pterostilbene (Pte) and 4′-Methoxyresveratrol (4MR) are methylated derivatives of resveratrol. We investigated the anti-inflammatory effect of Pte and 4MR in lipopolysaccharide (LPS)-stimulated RAW264.7 murine macrophages. Both Pte and 4MR significantly reduced LPS-induced nitric oxide release by inhibiting the inducible nitric oxide synthase mRNA expression. Moreover, both of them inhibited LPS-induced mRNA expression of inflammatory cytokines including monocyte chemoattractant protein (MCP)-1, interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Macrophages are a vital component of the immune system, and play a large role in inflammatory processes. As important immune cells, macrophages respond immediately to microbial infection and directly engulf or indirectly eliminate pathogens by releasing multiple inflammatory mediators [5]. Lipopolysaccharide (LPS), a major component of gram-negative bacterial cell walls, is one of the most potent stimulators of innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are a vital component of the immune system, and play a large role in inflammatory processes. As important immune cells, macrophages respond immediately to microbial infection and directly engulf or indirectly eliminate pathogens by releasing multiple inflammatory mediators [5]. Lipopolysaccharide (LPS), a major component of gram-negative bacterial cell walls, is one of the most potent stimulators of innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the cytotoxic effect of HES, cell viability assay was performed in HepG2 cells by MTT assay. When the cell viability is above 80%, the drug can be thought to have no significant cytotoxicity on cell growth (Johan, Gertjan, & Jacqueline, ; Xu et al, ; Yao, Liu, Zhao, Hu, & Wang, ). As shown in Figure , HES‐1 μmol/L,HES‐5 μmol/L, and HES‐25 μmol/L had no significant cytotoxicity in the HepG2 cells after 24 hr of treatment ( p ≥ .05).…”
Section: Resultsmentioning
confidence: 99%
“…iNOS and COX-2 coordinate with each other, directly damage the DNA and protein of cells, and play an important role in activating NF-κB. At present, many in vivo and in vitro experiments have shown that PTER can play a powerful anti-inflammatory role by inhibiting the NF-κB signaling pathway, which can mediate the regulation of a variety of inflammatory mediators, including COX-2, iNOS, TNF-α, IL-6 and IL-1β and so on ( Cichocki et al, 2008 ; Zhang and Zhang, 2016 ; Yao et al, 2018 ). It was found that p-p65 and p -IκB proteins in lung tissue of ALI mice were significantly higher than those in blank group.…”
Section: Discussionmentioning
confidence: 99%